Conversion to Total Hip Arthroplasty After Hip Arthroscopy: A Cohort-Based Survivorship Study With a Minimum of 2-Year Follow-up. Issue 20 (15th October 2021) - Hoit, Graeme; Whelan, Daniel B.; Ly, Patrick; Saskin, Refik; Atrey, Amit; Khoshbin, Amir
Abstract : Introduction: The purpose of this study was to determine which patient, provider, and surgical factors influence progression to total hip arthroplasty (THA) after hip arthroscopy (HA) through a large cohort-based registry. Methods: All patients ≥18 years who underwent unilateral HA in Ontario, Canada, between October 1, 2010, and December 31, 2016, were identified with a minimum of 2-year follow-up. The rate of THA after HA was reported using Kaplan-Meier survivorship analyses. A Cox proportional hazard model was used to assess which factors independently influenced survivorship. Results: A total of 2, 545 patients (53.2% female, mean age 37.4 ± 11.8 years) were identified. A total of 237 patients (9.3%) were identified to have undergone THA at a median time of 2 years after HA, with an additional 6.3% requiring a revision arthroplasty at a median time of 1.1 years. Patients who underwent isolated labral resection (hazard ratio [HR]: 2.55, 95% confidence interval [CI]: 1.51 to 4.60) or in combination with osteochondroplasty (OCP) [HR: 2.11, 95% CI: 1.22 to 3.88] were more likely to undergo THA versus patients who underwent isolated labral repair or in combination with an OCP, respectively. Older age increased the risk for THA (HR: 14.0, 95% CI: 5.76 to 39.1), and treatment by the highest-volume HA surgeons was found to be protective (HR: 0.55, 95% CI: 0.33 to 0.89). Discussion: Using our methods, the rate of THA after HA was 9.3% at 2 years. The rate of revision arthroplasty was 6.3% at 1 year. Patients who underwent labral resection, isolated OCP, and/or were of increased age were at increased independent risk of conversion to THA. Those treated by the highest-volume HA surgeons were found to be at reduced risk of conversion to THA.